A novel halogen‐free co‐curing agent with linear multi‐aromatic rigid structure as flame‐retardant modifier in epoxy resin. (10th October 2017) - Chen, Ting; Chen, Xianming; Wang, Meijie; Hou, Peixin; Jie, Cao; Li, Jilu; Xu, Yiting; Zeng, Birong; Dai, Lizong
Abstract : A novel halogen‐free 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO)‐containing co‐curing agent, 6, 6′‐(1, 4‐phenylenebis(((4‐(phenylamino)phenyl)amino)methylene))bis(dibenzo[c, e][1, 2]oxaphosphinine 6‐oxide) (DPN) was synthesized via a simple 1‐pot or 2‐step procedure with yield of 86.2% and 70.8%, respectively. The molecular structures of 4, 4′‐((1, 4‐phenylenebis(methanylylidene))bis(azanylylidene))bis(N‐phenylaniline) (DPN intermediate) and DPN are characterized by FTIR, NMR, and MS. TGA tests show that the char yield of DPN/EP composites raises to 30.9% when the molar ratio of DPN to 4, 4‐diaminodiphenyl methane(DDM) is 20:80. Tg values of DPN/EP composites tested by DSC and DMA are similar to neat epoxy resin (EP), which is due to the secondary amine in DPN that participates in the cross‐linking reaction of epoxy resin. The storage modulus in the rubber stage (E′‐190 °C) of flame‐retardant epoxy resin is close to that of neat EP, while their tanδ's are lower, which indicates the similarity of samples' cross‐linking density due to the participation of DPN in the cross‐linking reaction. The results show that when the molar ratio of DPN and DDM is 5:95, the epoxy has a higher Tg value and better mechanical properties than other samples. The introduction of DPN efficiently improves the flame‐retardant properties of epoxy resin with V‐0 rating of UL‐94 vertical burning test, non‐dripping, 41% of limit oxygen index (LOI) value, low peak heat release rate (PHRR), and total heat release (THR).